2015
DOI: 10.5897/err2015.2282
|View full text |Cite
|
Sign up to set email alerts
|

The mediation effect of school satisfaction in the relationship between teacher support, positive affect and life satisfaction in adolescents

Abstract: The aim of this study is to examine the relationships among teacher support, positive emotions, school satisfaction and life satisfaction in adolescences. The study had the participation of 344 adolescents from different socioeconomic levels studying in the sixth, seventh and eighth grades of three public middle schools in the province of Çanakkale. The study population consisted of 173 (50.3%) girls and 171 (49.7%) boys. The data from the study were collected with the School Climate Inventory, Scale of Positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
1
3
0
1
Order By: Relevance
“…The current study attempted to investigate relationships among school-related variables, demographics, and school satisfaction and identify predictors of school satisfaction in students aged 11–16 years in Jordan. The results were in line with previous studies in that they demonstrated the importance of peer, teacher, and parent support for perceived school satisfaction among adolescents 2,7,8,11,12,25. Our findings add to previous studies by extending findings to a sample that had not been researched before.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study attempted to investigate relationships among school-related variables, demographics, and school satisfaction and identify predictors of school satisfaction in students aged 11–16 years in Jordan. The results were in line with previous studies in that they demonstrated the importance of peer, teacher, and parent support for perceived school satisfaction among adolescents 2,7,8,11,12,25. Our findings add to previous studies by extending findings to a sample that had not been researched before.…”
Section: Discussionsupporting
confidence: 92%
“…Some of these predictors were reported to be more robust than others. For instance, teacher support is strongly presented in the literature as a predictor of school satisfaction 2,7,8,11. Moreover, one study showed that teacher likability is one factor behind student satisfaction with school, reflecting that students who like their teachers are more satisfied with their school setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, over the last years the role that satisfaction experienced during school life may have in the perception that children and adolescents have of their own global subjective well-being has been underscored (Casas, 2011). In a study conducted with 344 adolescents by Telef et al (2015) teacher support was observed to promote higher perceptions of school satisfaction, which in turn, influences global subjective well-being. Consequently, there was an indirect relationship between teacher support and subjective well-being through the mediator's role of school satisfaction.…”
Section: The Mediating Role Of School Satisfactionmentioning
confidence: 99%
“…Okul doyumu öğrencilerin yaşamlarında mutlu olmalarını sağlayan önemli doyum alanlarından biridir (Casas, Bello, González, ve Aligué, 2013;Telef, Arslan, Mert ve Kalafat, 2015). Okul doyumu, okul yaşamının nasıl algılandığının öznel ve bilişsel değerlendirilmesidir (Baker, Dilly, Aupperlee ve Patil, 2003).…”
Section: Introductionunclassified